Yield Gap Analysis of Chickpea Productivity through Front Line Demonstrations in Sagar District of Madhya Pradesh - A.K. Tripathi, K.S. Yadav, Mamta Singh; D.K. Singh (Indian Journal of Extension Education, 2018)
The frontline demonstrations on proven technology on chickpea was conducted on 80 farmer’s fields in the six villages of Sagar district of Bundelkhand region of Madhya Pradesh during rabi seasons of 2012-13 to 2013- 14 under rainfed condition on medium to heavy soil with medium fertility status. Demonstration was conducted under Soybean – Chickpea cropping system to study the productivity enhancement of Chickpea through improved production technologies. The results revealed that integrated crop management practices reduced the wilt incidence reduced from 10.45 to 4.05 per cent (61.2 per cent) and larval population of Gram pod borer decreased from 1.2 to 0.50 per plant (58.3 per cent) in both the years. The average 45-46 pods per plant were obtained under improved technology over to farmer’s practices (36-40). The seed yields of chickpea under improved technology ranged between 9.83 q ha-1 to 15.79 q ha-1 with increase in seed yields by 22.8 and 39.8 per cent in both the years. The average seed yields under improved technology were 12.81 q ha-1 as against farmers practice where seed yield was 9.94 q ha-1. On an average an additional cost Rs. 1376 ha-1 with improved package given additional benefits of Rs. 8795/ha from chickpea crop . However, maximum average net returns (Rs.37588 ha-1) as well as benefit cost ratio (4.61) were recorded under improved technologies as compared to farmer’s practice (Rs.28793 ha-1 and 4.18). Technology gap of 319 kg/ha and extension gap of 291 kg/ha were found in chickpea production due to differential in feasibility of recommended technologies, lack of awareness, timely unavailability of quality input at farmers level.